If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying bx + 6 = 18 Reorder the terms: 6 + bx = 18 Solving 6 + bx = 18 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + bx = 18 + -6 Combine like terms: 6 + -6 = 0 0 + bx = 18 + -6 bx = 18 + -6 Combine like terms: 18 + -6 = 12 bx = 12 Divide each side by 'x'. b = 12x-1 Simplifying b = 12x-1
| 1/3(2/5-2/3)w | | -2(5+2x)-3(5-5x)=-47 | | -240=-15v | | 2x-1=8x+17 | | 10x+13x=6 | | 4x-1=22(x+3) | | 7+3x=3x+8 | | 2(n+2)=5 | | 17-u=10 | | (3y-1)+(3x+2)= | | 1/2^-2x^-3y^5 | | 12+3x-5=8x+8-5x | | 2(w-4)=6 | | 4(2x-12)=16-3(X-4) | | 2/r=1 | | 12=4+4f | | 120/x=1,2954545455 | | 0.99d=10 | | 55=-2a+8a+1 | | ax+c=4b | | y=24-4x/3 | | 3x^2+15=75 | | 3.4y-5.2=3y | | 120/x=1,0714285714 | | 0=-4K-5k | | -4x+4+3=11 | | 8abc-2a(b-2)*a-(3a-b)*c=0 | | 6x^3-13x^2-73x-60=0 | | 24a^3c+16a^2c^2= | | M-15=12 | | 4(2X+8)-27-15X=29-12X+6 | | 8x+12=3x-5 |